Impact of choice attributes perceived by Korean airline passengers on relationship quality during the COVID-19 pandemic - Kim, Su Min; Park, Yoon Joo; Shin, Hyoung Chul (Nurture, 2024)
Purpose: This study investigates the relationship between the choice attributes of the passengers of a Korean airline and relationship quality during the COVID-19 pandemic in South Korea. Design/Methodology/Approach: This study used a quantitative approach and conducted an online survey using Google Forms through the convenience sampling method on users with experience in domestic and international airlines within the past month. It received 300 valid responses. The data were analyzed using Statistical Package for the Social Sciences version 21. Findings: This study hypothesized that a significant relationship exists between airline selection attributes and the quality of relationships. The results demonstrate that satisfaction significantly influences trust. Conclusion: This study demonstrated that choice attributes as perceived by passengers exert a significant influence on determining the quality of relationships between airlines and customers. Research Limitations and Implications: The data were collected using an online questionnaire due to the COVID-19 situation. This aspect is a limitation of the study because it is highly dependent on the honesty and willingness of the respondents. Practical Implications: This study found that airlines can improve the quality of relationships with customers by overcoming crises if they can increase satisfaction by grasping the selection attributes pursued by customers. This study suggests appropriate marketing strategies for airline managers in Korea.